El análisis de contenido como una metodología - Mendes, Rosana Maria; Miskulin, Rosana Giaretta Sguerra [UNESP] (FapUNIFESP (SciELO), 2017)
In this article we discuss content analysis as a method for analysing data of qualitative research in education. The method is a fundamental part of academic work, because it gives to the investigation some characteristics which are central to determine its quality. Thus, we present the “shades”, such as the scenario in which the study was conducted, the period and the environment in which an extension course took place (modules I and II), the choice of the software employed, the participants, the press conferences and the explanation of how data collection and oral and written records were produced. Data analyses were based on content analysis proposed by Bardin (1977) and Franco (2008). With this material, like bricoleurs or artisans sewing their patchwork, we went about building our research.
L’analyse de contenu comme méthodologie
A análise de conteúdo como uma metodologia
Keywords: Content analysis; Education; Mathematics; Qualitative research